2014
DOI: 10.1002/bmc.3247
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic study of biochemical changes in urinary of type 2 diabetes mellitus patients after the treatment of sulfonylurea antidiabetic drugs based on ultra‐performance liquid chromatography/mass spectrometry

Abstract: A metabonomic study on biochemical changes in the urine of type 2 diabetes mellitus (T2DM) patients after the treatment of sulfonylurea (SU) antidiabetic drugs was performed. An ultra-performance liquid chromatography/mass spectrometry (UPLC/MS) method was used to generate metabolic fingerprints for the metabonomic analysis of urinary samples obtained from 20 T2DM patients without any drug treatment and 20 T2DM patients treated with SU antidiabetic drugs and 20 normal glucose tolerance subjects. The resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…The role of the microbial community hosted by diabese subjects in altering choline metabolism was also tested by assessing the effects of antidiabetic medication ( Huo et al, 2009 ). As shown in Table 1 , Huo et al (2015) observed increased serum levels of TMAO in overweight diabetic subjects receiving metformin treatment versus untreated diabese controls, which may indicate an intestinal bacterial regulation function of metformin. It has already been suggested that antidiabetic treatments have a beneficial effect on gut microbiota metabolism ( Huo et al, 2015 ), although the exact mechanisms are still unclear ( Moreno-Navarrete et al, 2012 ).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The role of the microbial community hosted by diabese subjects in altering choline metabolism was also tested by assessing the effects of antidiabetic medication ( Huo et al, 2009 ). As shown in Table 1 , Huo et al (2015) observed increased serum levels of TMAO in overweight diabetic subjects receiving metformin treatment versus untreated diabese controls, which may indicate an intestinal bacterial regulation function of metformin. It has already been suggested that antidiabetic treatments have a beneficial effect on gut microbiota metabolism ( Huo et al, 2015 ), although the exact mechanisms are still unclear ( Moreno-Navarrete et al, 2012 ).…”
Section: Resultsmentioning
confidence: 78%
“…As shown in Table 1 , Huo et al (2015) observed increased serum levels of TMAO in overweight diabetic subjects receiving metformin treatment versus untreated diabese controls, which may indicate an intestinal bacterial regulation function of metformin. It has already been suggested that antidiabetic treatments have a beneficial effect on gut microbiota metabolism ( Huo et al, 2015 ), although the exact mechanisms are still unclear ( Moreno-Navarrete et al, 2012 ). The authors suggested a link between the deregulation of choline metabolism in T2D and a rupture of the intestinal barrier by oxidative stress ( Wei et al, 2008 ).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Recently, Huo et al reported the effect of SUs, including glimepiride, on metabolomic changes. [15] They used urine samples collected from normal group, non-treated patients with T2DM and SU-treated patients with T2DM. The samples were analyzed using the ultra-performance liquid chromatography/mass spectrometry method.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Recently, the effect of SUs on biochemical changes in patients with T2DM was investigated through the metabolomic approach. [15] However, the effects of glimepiride on endogenous metabolomic alterations in healthy subjects remain poorly understood.…”
Section: Transl Clin Pharmacolmentioning
confidence: 99%